2016
DOI: 10.1186/s11671-016-1690-4
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Nanomolybdenum Influence upon the Antioxidative Reaction of Chickpea Plants (Cicer arietinum L.)

Abstract: The use of colloidal solutions of metals as micronutrients enhances plant resistance to unfavorable environmental conditions and ensures high yields of food crops. The purpose of the study was a comparative evaluation of presowing treatment with nanomolybdenum and microbiological preparation impact upon the development of adaptive responses in chickpea plants. Oxidative processes did not develop in all variants of the experiment but in variants treated with microbial preparation, and joint action of microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…•at 480 nm in root and leaf tissues of the buckwheat plants (Boveris, 1984). The level of lipid peroxidation was evaluated by the accumulation of thiobarbituric acid reactive substances (TBARS) (Kumar & Knowles, 1993) with some modifications (Taran et al, 2016). Light absorption was recorded at 533 nm.…”
Section: Methodsmentioning
confidence: 99%
“…•at 480 nm in root and leaf tissues of the buckwheat plants (Boveris, 1984). The level of lipid peroxidation was evaluated by the accumulation of thiobarbituric acid reactive substances (TBARS) (Kumar & Knowles, 1993) with some modifications (Taran et al, 2016). Light absorption was recorded at 533 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The most important micronutrients are also heavy metals, and their excess can cause phytotoxicity (Taran et al, 2016). Treatment with different nanoparticle metal solution have a long-term effect of gradual growth of the chlorophyll index, dry matter accumulation and other important parameters of productivity (Son'ko et al, 2013;Islas-Valdez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mo is a cofactor of plant enzymes involved in N assimilation and rhizobial N fixation . A recent study demonstrated that a combination of Mo-NPs (0.8 mg g –1 ) and Ryzobofitom ( Rhizobium biofertilizer containing 8 Log CFU mL –1 cells) improved antioxidant activity in C. arietinum allowing better stress adaptation . Si is a normal component of soil and is deposited mainly in the endoplasmic reticulum, cell wall, and intercellular spaces of plant cells and helps alleviate biotic and abiotic stress. , SiO 2 -NPs are reported to be nontoxic to growth of Oryza sativa (rice), Z. mays , and L. esculentum . Si accumulation after application of SiO 2 -NPs is reported to contribute to drought tolerance in Z. mays and L. esculentum . SiO 2 -NPs enhanced leaf area, photosynthetic activity, proteins, phenols, and population of beneficial rhizobacteria (phosphate solubilizing bacteria, nitrogen fixers, and silicate solubilizing bacteria) in Z. mays . ,, All these studies are indicative of the rapid progress in the development of diverse types of micronutrient NPs and assessment of their effect on plant growth and physiology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have also reported that aggregates of NP with larger sizes are not taken up to the shoot, thereby eliminating the toxicity or restricting it to the root surface. , The negative effects of NPs containing Au, Ce, Si upon soil application have not been studied well and need to be evaluated due to their extensive use in commercial products, drug delivery systems, and industries and can lead to increased release in the soil environment. Studies have indicated that NPs containing Ca, Mo, Mg, and mineral nanoconjugates of chitosan and montmorillonite exhibited limited negative effects on plants after soil application. ,,, …”
Section: Introductionmentioning
confidence: 99%